2017
DOI: 10.1080/00103624.2017.1374402
|View full text |Cite
|
Sign up to set email alerts
|

Development and Nutrition of Soybeans with Macronutrients Deficiencies

Abstract: Soy is to one of the main crops in the world. However, there are aspects related to its management that should be explained, especially regarding its mineral nutrition, because a proper nutritional balance is associated with productivity levels. The objective of this study was to evaluate the accumulation of nutrients in the tissues related to the deficiency of nutrients and its effects on plant development. In addition, nutritional disorder symptoms were evaluated according to the deficiency of macronutrients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Virk et al [25] reported that soybean plant height was insignificantly enhanced by N application. 30.4% significant reduction in plant height as a result of N deficiency was reported [26]. Drought reduced the average SPAD values in both inoculated and noninoculated plants.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Virk et al [25] reported that soybean plant height was insignificantly enhanced by N application. 30.4% significant reduction in plant height as a result of N deficiency was reported [26]. Drought reduced the average SPAD values in both inoculated and noninoculated plants.…”
Section: Discussionmentioning
confidence: 94%
“…e application of N-fertilizer significantly increased LAI in soybean [25]. Caliskan et al [8] concluded that soybean LAI linearly increased with increased N rates, whereas de Almeida et al [26] found that the deficiency of N in soybean plants significantly decreased LAI by 87.5%.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Existe una relación directa entre el crecimiento de un cultivo y la disponibilidad de nutrientes solubles, es decir, disponibles para ser absorbidos por las raíces de las plantas. Rayar (1981, citado en Bruns, 2016 reportó que a partir de concentraciones de 0,25 mM de Ca se producen los máximos crecimientos de soja, pudiéndose encontrar disminuciones de hasta el 66%, según De Almeida et al (2017), debido a su baja disponibilidad. Wolt & Adams (1979) encontraron aumentos de MS superficial de maní (Arachis hypogaea L.) con concentraciones hasta 0,15 mM Ca en la solución nutritiva, aunque Zharare et al (2009) encontraron diferentes concentraciones óptimas de Ca para diferentes variedades de este cultivo, utilizando soluciones nutritivas entre 0,009 y 2,5 mM Ca.…”
Section: Introductionunclassified
“…The distribution of light reception can be observed by observing leaf area and leaf area index, of which an optimum leaf area index will result in efficient use of resources in plants and lead to a high assimilate production to promote the growth rate of plants (Zakariyya, 2016;Srinivasan et al, 2017). However, according toZaman and Asaeda (2014); Almeida et al (2017), the formation of leaf assimilates is determined not only by the acceptance of light, but also determined by macro and micro nutrients which play a role in the preparation of the element or the formation of assimilates. Results of research by Kusdianti et al (2014); Shah et al (2017); Paunov et al (2018) revealed that cadmium (Cd) uptake by plants may inhibit the formation of leaf chlorophyll thus affecting plant biomass products.…”
Section: Introductionmentioning
confidence: 99%